Sociolinguistic Epistemology and Its Implications in Learning Indonesian Language at School - Sihombing, Novita Asmi; Sauri, Sofyan (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2021)
Epistemology is one of the three branches of philosophy that deals with science besides ontology and axiology. This scientific foundation is related to the use of this knowledge in order to meet human needs. Language and society can never be separated from one another, because where there is society, there is language, and vice versa. The existence of language in society is studied through sociolinguistics, which sees language as a means of communication between community members with variations according to their social sphere. On the other hand, traditional language teaching views language as a system, thus giving birth to structuralist language teaching. During its development, the proponents of the language teaching method realized that language was not just a system, but rather a means of communication, as studied through sociolinguistics. This study discusses the role of sociolinguistics in the development of language teaching, starting from the characteristics of the language community, language functions, to sociolinguistic-based language teaching models. The material in language teaching also reviews the contribution of sociolinguistics in providing language teaching materials from a sociolinguistic point of view. Keywords: Epistemology, Sociolinguistics, Language Teaching